An Entrepreneurial Business Model for Personal Branding: Proposing a Framework - Raftari, Mehdi; Amiri, Behrooz (Journal of Entrepreneurship, Business and Economics, 2014)
Purpose- Personal branding has become a mature field of research; however, there are many ques-tions to be answered yet. One of the most important questions is that what does a typical entrepre-neurial business model look like? Design/methodology/approach- To answer the above question, the present paper tries to use meta-analysis approach to making an integrated view of the extant literature. Thus, 25 papers, which were mainly focusing on the topic, was selected and critically reviewed. Finally, a framework is proposed based on Osterwalder's (2004) approach. Findings- Findings of this research are mainly focused on the characteristics of each dimension in the entrepreneurial business model for personal branding. Research limitations/implications- Research implications imply that a typical entrepreneurial busi-ness model for personal branding might be helpful for both entrepreneurs as well as policy makers. Research paper Reference to this paper should be made as follows: Raftari, M. and Amiri, B. (2014). ―An Entrepre-neurial Business Model for Personal Branding: Proposing a Framework‖, Journal of Entrepreneur-ship, Business and Economics, Vol. 2, No. 2, pp. 121–139.